Regulatory Model Traditional Markets, Shopping Centers, and Modern Shops Based on Justice in Karangasem Regency, Bali Province - Wibawa, Sastra; Arthadana, Gede Made; Artatik, I Gusti Ayu Ketut (Universitas Muhammadiyah Yogyakarta, 2026)
Development in Karangasem Regency is currently classified as being in an increasingly developed stage. Chain store proliferation has led to traditional markets and even retail traders competing for the people's choice in shopping. In addition, supermarkets, chain stores, and shopping centers raise concerns about the future of Traditional Markets. Legal protection for business actors was indeed created to enable competition and promote healthy competition, as well as to prevent business monopolies, especially among traditional market players. This study is necessary as a guideline and technical reference for stakeholders in organizing and fostering networked stores by examining changes in current regulations. This study is included in the type of normative legal research or doctrinal legal research. The discussion was conducted through several approaches, including the legislative approach, the legal concept approach, and the legal analysis approach. So that with consideration of the social and economic conditions of the surrounding local population, aspects of distance and aspects of zoning of spatial planning, aspects of licensing, and aspects of operational hours as the basis for regulating the Shopping Centers and Modern Stores, it is hoped that later it can bring a sense of justice to Traditional Market actors in the surrounding area. In the future, it is necessary to pay attention to economic aspects, Zoning, Licensing, Operating Hours, Taxes, and Regional Retributions. In general, the opening of Modern Network Stores is still possible in Karangasem Regency in all Districts.